Proposta de ensino de geometria analítica utilizando o Desmos - Euzébio, Julian da Silva (2018)
In this dissertation we investigated the possibility of teaching and learning some contents of Analytical Geometry with the use of Desmos software. Desmos is a graphical calculator available free of charge to all interested parties, designed by Eli Luberoff, in 2007. In order to better understand the possibilities of improving the teaching and learning process of mathematics contents with Desmos software, we created a sequence of interactive activities covering various topics of Analytical Geometry for high school. The activities presented in this dissertation are arranged sequentially, so that other stakeholders have no difficulties in executing them. The research also shows the positive results of the use of this type of resource and the analysis of an applied experience of a content in a high school of the municipality of Dois Vizinhos, Paraná.